Penerapan Metode Demonstrasi pada Pembelajaran Akidah Akhlak dalam Meningkatkan Pemahaman Siswa - Suriyati; Agustina (Faculty of Tarbiyah and Teacher Training, 2024)
Students' weak ability to understand learning is a common obstacle in school learning activities, so more effective learning methods are needed. This article aims to understand how to apply the demonstration method in teaching Aqidah Akhlak to improve the understanding of class XI students at MAN 1 Sinjai. The research method applied is classroom action research (PTK), which has four stages: planning, action, observation and reflection. The subjects in this research were 26 students of class XI Biology at MAN 1 Sinjai. The results of this research show that using the demonstration method can improve or develop students' understanding of class XI Biology MAN 1 Sinjai on the subject of moral beliefs. Based on the evaluation results of each cycle, the scores obtained by students through observations of teacher activities can be revealed. If learning in cycle I got an average score of 74.5, then in cycle II, the average score was 88.5. Students who met the criteria Minimum Completeness with 90.33% completeness with an average score of 80.88 in the range of 81-100 is considered very high. This research implies that applying the demonstration method can increase students' understanding of learning moral beliefs and can help students understand the material better than just reading text or listening to verbal explanations.